2003
DOI: 10.1161/01.atv.0000085040.58340.36
|View full text |Cite
|
Sign up to set email alerts
|

VLDL Induces Adipocyte Differentiation in ApoE-Dependent Manner

Abstract: Objective-To clarify the role of very low density lipoprotein (VLDL) and apolipoprotein E (apoE) in adipogenesis, we studied newly developed hyperlipidemic obese (ob/ob;apoE Ϫ/Ϫ ) mice. Because hydrolysis of VLDL is believed to be the major source of adipogenic free fatty acids, a higher plasma level of VLDL in these mice should exaggerate obesity. Methods and Results-When fed a high-fat, high-cholesterol diet, ob/ob;apoE Ϫ/Ϫ mice did not show increased body weight or an increased amount of adipose tissue in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
67
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(79 citation statements)
references
References 44 publications
9
67
0
2
Order By: Relevance
“…Insulin sensitivity was markedly greater in apoE Ϫ/Ϫ ;Ay/ϩ than in apoE ϩ/ϩ ;Ay/ϩ mice. Recently, several attempts to induce obesity in apoE Ϫ/Ϫ mice have been reported, but the results have been somewhat controversial (12)(13)(14). In the present study, in addition to inhibition of adiposity and insulin resistance with apoE deficiency, adenoviral apoE replenishment reversed inhibition of obesity and glucose intolerance.…”
Section: Discussionsupporting
confidence: 43%
See 3 more Smart Citations
“…Insulin sensitivity was markedly greater in apoE Ϫ/Ϫ ;Ay/ϩ than in apoE ϩ/ϩ ;Ay/ϩ mice. Recently, several attempts to induce obesity in apoE Ϫ/Ϫ mice have been reported, but the results have been somewhat controversial (12)(13)(14). In the present study, in addition to inhibition of adiposity and insulin resistance with apoE deficiency, adenoviral apoE replenishment reversed inhibition of obesity and glucose intolerance.…”
Section: Discussionsupporting
confidence: 43%
“…We have recently reported that alterations in metabolism in adipose tissue affect food intake amounts (19). However, ob/ob;apoE Ϫ/Ϫ mice are also reportedly resistant to obesity (14). Since ob/ob mice are leptin deficient, the obesity resistance in ob/ob;apoE Ϫ/Ϫ mice is not mediated by leptin signaling, e.g., leptin sensitization, although food intake and energy expenditure were not measured in the earlier study (14).…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Real-time PCR was carried out using the Light Cycler (Roche Diagnostic GmbH, Mannheim, Germany) and the SYBR green PCR kit (Qiagen Inc., CA, USA), as described previously 19) . The gene-specific oligonucleotide sequences were as follows.…”
Section: Real-time Pcrmentioning
confidence: 99%